ANALISIS KEPATUHAN PERPAJAKAN PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) SETELAH PENERAPAN PERATURAN PEMERINTAH NO. 23 TAHUN 2018 - Elvira Anggreini; Rasidah; Wahyudin Nor (Universitas Lambung Mangkurat, 2021)
This study aims to determine the level of compliance of MSME taxpayers on tax obligations, determine the factors that influence the level of tax compliance of MSME taxpayers and determine the efforts made by KPP Pratama Banjarmasin to improve tax compliance. The results showed that the level of MSME tax compliance in KPP Pratama Banjarmasin after the enactment of PP No. 23 of 2013 was still relatively low, many factors influenced the MSME tax compliance level, one of which was an understanding of Self Assessment and efforts to improve tax compliance of MSME actors, one of which was giving a warning letter.